DEVELOPMENT AND VALIDATION OF BIOANALYTICAL METHOD FOR QUANTIFICATION OF PINOLINE AND ITS METABOLITE 6-OH-1,2,3,4-TETRAHYDROCARBOLINE FOR THE PURPOSE OF CYPD26 ACTIVITY DETERMINATION - R. K. Abdrashitov; A. E. Petukhov; V. V. Smirnov (Разработка и регистрация лекарственных средств, 2019)
A sensitive method for quantification of pinoline and its metabolite in human plasma using solid phase extraction and high performance liquid chromatography with mass-spectrometry was developed. Analytical range was 250-1500 pg/ml both for pinoline and for 6-hydroxy-1,2,3,4-tetrahydro-β-carboline. The developed method may be used to determine the current status of CYP2D6 activity.